Evaluation of the machinability and enhancement of biological response of ZTA-based 13–93 bio-glass composite materials - Singh S.K.; Singh P.; Mahapatra D.; Dubey A.K.; Pyare R.; Roy P.K. (My University, 2025)
Besides the exceptional mechanical and biocompatible properties, zirconia toughened alumina (ZTA) has limited biomedical applications due to its bio-inertness properties. The present work examines the effect of 13–93 bio-glass (BG) addition on the machinability and biological responses of ZTA-containing BG composites. The ZTA–xBG (x = 0, 5, 10, 15, and 25 wt%) composites have been synthesized and sintered at 1250 °C for 4 h. The machining of composite samples is done on an abrasive air-jet machine (AAJM), and their machinability is studied in terms of surface roughness (SR), material removal rate (MRR), and mechanics of material removal (MMR). The result indicates that MRR decreases and SR enhances with the addition of BG. The MMR is studied using machined surface morphology, and the results confirm that material removal is due to the large erosion crater. The relative density is decreased with enhancing the BG content except for a sample containing a high amount of BG (25 wt%). Mechanical properties such as hardness and flexural strength are enhanced by BG content up to 25 wt%. In-vitro analysis in simulated body fluid (SBF) reveals that both corrosion and bioactivity increase as BG concentrations increase. According to the in-vitro cell culture data, adding BG to ZTA improves cellular viability with BG content up to 25 wt%. The antibacterial result shows that the viability of the bacterial cells on the composites has significantly decreased with BG content. As a result, biomaterials with this architecture may be used as bone implants. © 2024 Elsevier B.V.